Salmonelose em répteis: aspectos epidemiológicos, clínicos e zoonóticos - Fornazari, Felipe; Teixeira, Carlos Roberto [UNESP] (My University, 2009)
Salmonellosis is a disease caused by bacteria of Salmonella genus, which infect many species of animals and man. Reptiles are considered the main reservoir, and may develop the disease under determinate conditions. The symptoms are unspecific, and the microbiologic culture is the most common method. The treatment is poorly efficacious and advisable only in cases of clinical signs manifestation. The transmission from reptiles to human may occur, and prophylactic measures that involve good hygiene practices and the control of the disease in animals has special importance.
Salmonellosis in reptiles: epidemiologic, clinical and zoonotic aspects.